PENGARUH GENDER, PERSEPSI MANAJEMEN DAN PROFITABILITAS PADA PENCAPAIAN SDGS MELALUI SUSTAINABILITY REPORTING - Wiwik Saraswati; Dwi Susilowati; Juwari Juwari; Dimas Rama Pramudia; Amelia Dwi Anita (Jurnal GeoEkonomi, 2023)
Public awareness of the environment caused by the industrial activities of large companies, makes the public need information about the extent to which companies are responsible for the damage. SDGS voiced by the UN to be carried out in all countries, including Indonesia, must declare SDGS. This study seeks to find how women's representation in the leadership of a company can be one of the drivers of companies to be more concerned with voluntary disclosure, managerial roles and profitability in achieving Sustainable Development Goals (SDGs) in companies that are reflected in Sustainability Reporting (SR). The results showed that the presence of women on the board of directors did not affect the disclosure of SDGs. While managerial roles and profitability had a significant effect on the disclosure of SDGs.